2008
DOI: 10.1021/ma7025308
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Partially Protected Block Copolymers Based on 4-Hydroxystyrene Using NMRP and a Sequence of Polymer Analogous Reactions

Abstract: We present the synthesis and characterization of a family of partially protected block copolymers and their precursors synthesized by means of nitroxide mediated radical polymerization (NMRP) and a sequence of quantitative and orthogonal polymer analogous reactions. The target materials consist of an unprotected 4-hydroxystyrene block and a tert-butoxycarbonyl (BOC) or a tert-butyl (TBU) protected block. Corresponding precursor block copolymers exhibit low polydispersity indexes (PDI) (<1.36) and show well-def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2008
2008
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 41 publications
1
26
0
Order By: Relevance
“…225 They expanded this work to include poly(propargyloxystyrene) by using the TMS protecting group and demonstrated that the diversity of structure can be expanded by using “click” chemistry to further modify the block of poly(propargyloxystyrene). In addition to functionalizing this block with bulky groups, such as 1-adamantane azide 226 , they have reported the preliminary synthesis of diblock copolymers including a block of dendronized polymer prepared using CuAAC via the “grafting onto” approach (Scheme 47).…”
Section: Polymers From Reo Chemistriesmentioning
confidence: 99%
“…225 They expanded this work to include poly(propargyloxystyrene) by using the TMS protecting group and demonstrated that the diversity of structure can be expanded by using “click” chemistry to further modify the block of poly(propargyloxystyrene). In addition to functionalizing this block with bulky groups, such as 1-adamantane azide 226 , they have reported the preliminary synthesis of diblock copolymers including a block of dendronized polymer prepared using CuAAC via the “grafting onto” approach (Scheme 47).…”
Section: Polymers From Reo Chemistriesmentioning
confidence: 99%
“…18 With TIPNO-Sty as initiator and acetic anhydride as accelerator, the bulk reactions at 120°C result in final conversions of 70-80%. A good control over the molar mass varying from 7200 g/mol (MI-1a) to 43 700 g /mol (MI-3) was found and the MIs are characterized by low polydispersity indices (Table 1).…”
Section: Diblock Copolymersmentioning
confidence: 99%
“…[30] Furthermore, our approach resorting predominately to partly protected hydroxystyrene diblock copolymers synthesized by controlled radical polymerization (CRP) techniques has demonstrated that functionalized nanostructured surfaces can be successfully prepared. [31,32] In this communication, we would like to present a way how to efficiently post-modify a polymeric surface by click chemistry and to verify the chemical reaction even in very thin films by appropriate spectroscopic means. In our approach we developed a novel well-defined alkyne containing terpolymer that was prone to be tethered onto silicon substrates.…”
Section: Introductionmentioning
confidence: 99%